2019
DOI: 10.47602/jpsp.v3i2.172
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy with Ecological Systems Theory: Addressing Muslim Mental Health Issues and Wellbeing

Abstract: Muslims across the word underutilize mental health services for addressing their wellbeing and biopsychosocial, spiritual, and contextual issues. By 2030, the global Muslim population is expected to reach 2.2 billion people. This indicates that Muslim mental health is gaining importance and would require contextually (i.e., spiritually, culturally, empirically) more effective services. Practitioners used Acceptance and Commitment Therapy (ACT) and Ecological Systems Theory (EST) to promote wellbeing and addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(186 citation statements)
references
References 96 publications
5
151
0
16
Order By: Relevance
“…The findings also revealed that college belonging and social support mitigated the effect of it on spiritual wellbeing, which was consistent with the evidence from previous research, indicating that individuals with high levels of social support and belongingness reported greater spiritual wellbeing (Alorani and Alradaydeh 2018 ; Tanhan and Strack 2020 ; Weber and Cummings 2003 ). The need to belong is an essential psychological need for the human being that helps people to deal with adverse experiences (Baumeister and Leary 1995 ; Deci and Ryan 1985 ; Tanhan 2019 ). Specifically, school or college belonging has been linked to a variety of adjustment and wellbeing outcomes, such as fewer depressive symptoms, less loneliness, and greater life satisfaction (Civitci 2015 ; Mounts 2004 ; Pittman and Richmond 2007 ; Tanhan 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings also revealed that college belonging and social support mitigated the effect of it on spiritual wellbeing, which was consistent with the evidence from previous research, indicating that individuals with high levels of social support and belongingness reported greater spiritual wellbeing (Alorani and Alradaydeh 2018 ; Tanhan and Strack 2020 ; Weber and Cummings 2003 ). The need to belong is an essential psychological need for the human being that helps people to deal with adverse experiences (Baumeister and Leary 1995 ; Deci and Ryan 1985 ; Tanhan 2019 ). Specifically, school or college belonging has been linked to a variety of adjustment and wellbeing outcomes, such as fewer depressive symptoms, less loneliness, and greater life satisfaction (Civitci 2015 ; Mounts 2004 ; Pittman and Richmond 2007 ; Tanhan 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that having social support resources (e.g., friends, family) with whom fulfilling and meaningful relationships positively affect young adults’ spiritual wellbeing despite childhood maltreatment. People’s social support assets, therefore, improve their ability to cope with adversities (Arslan 2018b ; Cohen 2004 ; Tanhan 2019 ) by fostering resilience (Yıldırım and Çelik-Tanrıverdi 2020 ), and these assets also help them to receive support from others and to exhibit help-seeking behaviors in dealing with these experiences (Barker et al 2005 ; Schwarzer and Knoll 2007 ). Consistent with the findings of this study, studies reported that having social support was associated with better mental health and wellbeing (Arslan 2017c ; Arslan 2018b ; Arslan and Coşkun 2020 ; Bloom et al 2001 ; Cohen 2004 ; Cohen and Wills 1985 ; Kansky and Diener 2017 ; Tanhan 2020 ; Ye et al 2020 ), including college students’ spiritual wellbeing (Alorani and Alradaydeh 2018 ; Tanhan and Strack 2020 ; Weber and Cummings 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial development and validation of the School Belongingness Scale. Child Indicators Research, 10(4), 1043-1058. https://doi.org/10.1007/s12187-016-9414-y Arslan, G., & Tanhan, A. (2019).…”
Section: Variablesmentioning
confidence: 99%